Carnivàle - The Complete Second Series Episode 1-12 - Garcia, Rodrigo; Podeswa, Jeremy; Patterson, John D.; Denault, Jim; Glennon, James; Reiker, Tami; Stahl, Nick; Brown, Clancy; Barbeau, Adrienne (Warner, 2006)
Carnivale follows the travels of a roving carnival during the 1930's Dust Bowl. This group of odd characters pick up a mysterious young man who becomes the focus in a battle between good and evil. [www.tvrage.com]